Efficacy of Yougui pill combined with Buzhong Yiqi decoction in alleviating the sexual dysfunction in female rats through modulation of the gut microbiota. (1st January 2022) - Wang, Yangyun; Shi, Chaoliang; Yu, Wandong; Jiao, Wei; Shi, Guowei
Abstract: Context: Yougui pill combined with Buzhong Yiqi decoction (YPBYD) is used to relieve sexual dysfunction in clinical practice. Objective: To investigate changes in microbial composition caused by sexual dysfunction and identify dominant bacteria related to YPBYD treatment. Materials and methods: Female Sprague-Dawley rats were randomly divided into four groups ( n = 6): one group underwent Sham operation (Sham group), while three groups underwent ovariectomy (one model and two treatment groups). The ovariectomized (OVX) rats received oestradiol benzoate (250 µg/kg/week) or YPBYD (3.6 mL/d) via oral gavage for 4 weeks. Vaginal smear assay was performed; the serum levels of cyclic adenosine monophosphate (cAMP) and oestradiol (E2) were measured, followed by collection of stool samples for 16S rRNA sequencing. Results: After YPBYD treatment, the levels of E2 and cAMP in OVX rats significantly increased (E2: from 20.45 ± 1.60 ng/L to 24.38 ± 1.70 ng/L; cAMP: from 261.41 ± 9.21 pg/mL to 373.75 ± 17.37 pg/mL). OVX treatment decreased diversity of gut microbiota and YPBYD treatment restored gut microbiota composition. Compared with Sham group, the abundance of Romboutsia significantly increased, while those of Proteobacteria and Staphylococcus markedly decreased in OVX group (all p < 0.05); meanwhile, the abundance of these microbes showed an opposite trend after YPBYD treatment. These microbiotas were involved in tyrosine and tryptophan biosynthesis and fatty acid metabolism. Discussion and conclusions: These findings are the first to indicate YPBYD can alleviate female sexual dysfunction by modulating gut microbiota in OVX rats, which will help enhance the understanding on potential mechanism of YPBYD against sexual dysfunction.